Evaluation of heavy metal fixation ability from drilling waste of oil and gas wells using treated sugarcane bagasse - Saffarian, Farhad; Hosseini, Seyed Ahmad; Mohammadi Roozbahani, Maryam; Etminan, Alireza (Frontiers in Environmental Science, 2024)
The drilling industry is one of the main sectors of the oil industry and one of the most specialized industrial activities. Huge quantity production of sugarcane baggase in Khuzestan province make environmental opportunity to utilize this agricultural byproduct in different section as valuable byproduct. Followed aim in present study was investigation the ability of raw form of baggase and its transformed structure in heavy metals fixation in drilling mud. The present study was conducted with the aim of investigating the efficiency of crude bagasse, processed bagasse and biochar adsorbents in removing heavy metals from the drilling mud residues of Ahvaz oil field. Sampling of drilling mud waste from Mishan Geological Formation (MGF) and Aghajari Geological Formation (AGF) was done on a vibrating sieve. The treatments examined in this research include contact time in 6 levels (30, 60, 90, 120, 150 and 180 minutes), amount of adsorbent in 3 levels (0.1, 0.5 and 1g), adsorbent type in 3 levels (crude bagasse, processed bagasse and biochar), the formation type was in 2 levels (Aghajari and Mishan). After chemical digestion, the samples were placed in contact with Crude bagasse, processed bagasse and biochar according to the designed conditions. Then, the removal percentage of Ba, Ni, V, Cd, Fe and Pb metals was calculated. Means were compared using Duncan's test at the 1% level. The results showed that biochar adsorbent is the most efficient compared to other adsorbents. The maximum removal percentage of heavy metals Ba, Ni, V, Cd, Fe and Pb by crude bagasse is 72.53%, 68.89%, 79.49%, 76.88%, 49.42% and 85% respectively. Also, the results showed that the maximum removal percentage of heavy metals Ba, Ni, V, Cd, Fe and Pb by crude bagasse is 81/72%, 83/89%, 86/67%, 83/44%, 64/41% and 90.72% respectively. The maximum efficiency of biochar for adsorbing heavy metals Ba, Ni, V, Cd, Fe and Pb is also 90.70%, 91.84%, 88.89%, 88.75%, 78.59 %, and 97.75% obtained respectively. The maximum percentage of heavy metals adsorbed by all adsorbents was obtained in the amount of 1 gr/L.